PENGARUH FOMO, YOLO DAN LITERASI KEUANGAN TERHADAP KECENDERUNGAN MAHASISWA MENGGUNAKAN LAYANAN PAYLATER - Novian Laras Kristiana; Rispantyo Rispantyo (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aims to examine the influence of FOMO, YOLO, and financial literacy on the use of Paylater services among university students. A quantitative method was employed, using questionnaires distributed to 100 respondents, and the data were analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that, partially, FOMO does not have a significant effect, whereas YOLO and financial literacy have a significant impact. Simultaneously, all three variables influence the use of Paylater, suggesting that a lifestyle oriented toward enjoying the present and students’ financial understanding affect their decisions to use Paylater services.